PERAN PENDIDIKAN DALAM PEMBENTUKAN MORAL SISWA DI SEKOLAH DASAR - Lailatuz Zahra; Ulfa Rizkika; Zelhendri Zen; Desyandri Desyandri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The formation of moral character among elementary school students is a crucial aspect of education because, at this stage, values, attitudes, and positive habits begin to develop more consistently. A rapidly changing social environment, combined with technological advancements that provide unrestricted access to information, requires schools to play a strategic role in cultivating moral values in a directed and sustainable manner. This study aims to explore the role of education in shaping the moral character of students in elementary schools. The method employed is a literature study, also known as a library research approach, which involves collecting data and information by reviewing and analyzing scholarly articles and scientific journals. The findings indicate that the educational process is essential for fostering morally upright individuals. Through education, moral development is expected to progress appropriately, harmoniously, and in accordance with norms, human dignity, and fundamental values. As human beings are creatures who can be educated, education becomes a necessity. Thus, education plays a vital role in shaping the moral character of individuals.